Complex Colorblindness in Police Processes and Practices. (18th March 2020) - Welsh, Megan; Chanin, Joshua; Henry, Stuart
Abstract: Racial disparities in police-community encounters are well documented, with people of color experiencing higher levels of police scrutiny. Far less is known about how police officers perceive the racial dynamics at play in their work. As part of a 2016 study of traffic stops in San Diego, we conducted in-depth interviews with 52 city police officers. Despite evidence of racial disparities in SDPD practices related to post-stop outcomes, officers denied, minimized, or even condemned racial profiling during traffic stops; officers described operating under a neutral policy of "colorblindness." Our analysis identifies cognitive and discursive mechanisms which explain this complex and contradictory picture. We find that officers' accounts excuse, justify, or otherwise negate the role of race in routine police work, yet officers' thoughts and actions are based on racialized and, at times, dehumanizing narratives about people and communities of color. These morally neutral accounts form a pattern of micro-racialized discourse, constituting a layering of racialized processes and practices that cumulatively produce racially disparate outcomes. We argue that rejection of explicit racism alone is insufficient to address the progressive micro-racial aggression that emerges at key points during police-community encounters. We discuss the implications for law enforcement policy and practice.